Social Emotional Development Of Children Outside Of Marriage At Rejoso Metal Islamic Boarding School Pasuruan - Masita, Dewi; Laila, Itsna Noor (International Conference on Islamic Studies, 2022)
This study aims to find out in depth about the social and emotional development of children out of wedlock at the Rejoso Metal Islamic Boarding School, Pasuruan. The informants of this research are the kiai and ustad of the Metal Islamic Boarding School Rejoso Pasuruan and children out of wedlock, in this case they are students from the pesantren. This research methodology uses descriptive phenomenology with a psychological approach. The process of collecting data through interviews, observation, and documentation. Technical analysis of the data through the Horizontalizatio stage, Developing clusters of meaning, Textural description, Structural description, and Essentialization, Theory as an analytical tool using Hurlock's theory of social development. The results of this study indicate that the personality and social emotional formation of children outside of marriage is education and training (Riyadhoh) which is applied by the kiai and accompanied by the clerics. As well as making the position of the kiai as their parents and fellow students as their brothers, so that they feel they have a family who is ready to pay attention to their social and emotional development until they are adults. The implication of the theory is that the real family is not fixed on a biological family as Hurlock suggested, but people who are able to provide a feeling of security to a stable group, able to be relied on to meet their needs, a source of love and acceptance, who are not affected by what they do, guide them. teach socially approved behavior, able to help solve problems faced by each child in adjusting to life, so as to achieve success in social life, accept aspirations, develop talents and abilities able to be friends.